Spin‐Mixing Enhanced Proximity Effect in Aluminum‐Based Superconductor–Semiconductor Hybrids. Issue 33 (14th July 2022) - Mazur, Grzegorz P.; van Loo, Nick; Wang, Ji‐Yin; Dvir, Tom; Wang, Guanzhong; Khindanov, Aleksei; Korneychuk, Svetlana; Borsoi, Francesco; Dekker, Robin C.; Badawy, Ghada; Vinke, Peter; Gazibegovic, Sasa; et al.
Abstract: In superconducting quantum circuits, aluminum is one of the most widely used materials. It is currently also the superconductor of choice for the development of topological qubits. However, aluminum‐based devices suffer from poor magnetic field compatibility. Herein, this limitation is resolved by showing that adatoms of heavy elements (e.g., platinum) increase the critical field of thin aluminum films by more than a factor of two. Using tunnel junctions, it is shown that the increased field resilience originates from spin‐orbit scattering introduced by Pt. This property is exploited in the context of the superconducting proximity effect in semiconductor–superconductor hybrids, where it is shown that InSb nanowires strongly coupled to Al/Pt films can maintain superconductivity up to 7 T. The two‐electron charging effect is shown to be robust against the presence of heavy adatoms. Additionally, non‐local spectroscopy is used in a three‐terminal geometry to probe the bulk of hybrid devices, showing that it remains free of sub‐gap states. Finally, it is demonstrated that proximitized semiconductor states maintain their ability to Zeeman‐split in an applied magnetic field. Combined with the chemical stability and well‐known fabrication routes of aluminum, Al/Pt emerges as the natural successor to Al‐based systems and is a compelling alternative to other superconductors, whenever high‐field resilience is required. Abstract : In superconducting quantum circuits, aluminum is one of the most widely used materials. Aluminum‐based devices suffer from poor magnetic field compatibility. In this article, this limitation is resolved by showing that adatoms of heavy elements (e.g., platinum) increase the critical field of thin aluminum films by more than a factor of two.